STRATEGI PEMASARAN DIGITAL & WEBSITE UNTUK PROMOSI PRODUK RISET ALAM - Manera, Belinda; Muizu, Wa Ode Zusnita (LPPM STIE Muhammadiah Bandung, 2025)
Universitas Padjadjaran focuses on research and development of natural fiber-based products, particularly ramie. To promote herbal products under the PHI Herbal brand, an effective marketing strategy is essential to enhance visibility and public awareness. This study aims to evaluate and implement digital marketing strategies through social media and the official website to expand reach, increase audience engagement, and convert awareness into purchases. A qualitative approach is employed, involving the application of digital marketing strategies via Instagram and the website. Data is collected through social media interaction analysis, website traffic monitoring, and descriptive reports on the achieved results. The findings indicate increased engagement on Instagram, including a rise in followers and likes, as well as improved website traffic, although visitor numbers remain limited. The study highlights the need for content optimization and enhanced user interaction to improve marketing effectiveness and conversion rates. This research emphasizes the crucial role of digital marketing in bridging academic knowledge with practical industry applications and underscores the necessity for further development to expand PHI Herbal’s market reach.